2013
DOI: 10.1615/plasmamed.2014008194
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evidences on Synergy of Gas Discharge Agents in Bactericidal Activity of Nonthermal Plasma

Abstract: Nonthermal plasmas (NTPs) represent a new class of sterilizing agents. A full set of NTP bioactive factors includes electric components (E, charged particles and electric field), neutral active particles (R), and UV. A specific construction of the direct current (DC) corona source was used that allowed dissection of NTP bioactive factors and quantitative evaluation of their individual and combined action on bacterial pathogens Pseudomonas aeruginosa and Staphylococcus aureus. 10 and 120 s were required for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Untreated DI water retained a conductivity of 0 mS/cm 3 , even after 24 hours. The absence of change in the perturbations introduced in the conductivity of DI water post treatment showed that the conductivity created is a consequence of oxygen and nitrogen species rather than ions, which have a life span on the order of nanoseconds to milliseconds 41 , 49 . Therefore, the effects of ions in aqueous environments may be discounted as playing an important role.…”
Section: Resultsmentioning
confidence: 99%
“…Untreated DI water retained a conductivity of 0 mS/cm 3 , even after 24 hours. The absence of change in the perturbations introduced in the conductivity of DI water post treatment showed that the conductivity created is a consequence of oxygen and nitrogen species rather than ions, which have a life span on the order of nanoseconds to milliseconds 41 , 49 . Therefore, the effects of ions in aqueous environments may be discounted as playing an important role.…”
Section: Resultsmentioning
confidence: 99%